Properties of nail withdrawal holdings on Sentang timber (azadirachta excelsa) / Sasatul Nabi'ah Mohd Fuzi - Mohd Fuzi, Sasatul Nabi'ah (Faculty of Applied Sciences, 2017)
This study was conducted to test the nail withdrawal holdings on Sentang timber. Sentang (Azadirachta excelsa) were choose as a raw material because of the plantation species which fast growing tree. Fifty-four samples were determined in this study. The dimensions of the samples were (50 x 50 x 100) mm was prepared. Carbon metal type of nails with sizes of diameter and length at 3.16 x 77.85 mm for screw shank nail, 2.87 x 73.08 mm ring shank nail and 3.36 x 62.33 mm for smooth shank nail were used in the study. The data of withdrawal resistance of three types of nails were represented in maximum load, N. the nails were tested according to ASTM D1761- 2012 standards. Results show the highest value of nail withdrawal strength found in screw shank nails followed by smooth shank nail and ring shank nail. Between three types of nails, they are not significant different strength.